Protected designation of cheese origin - Neven Antunac; Jasmina Havranek; Dubravka Samaržija; Marija Pecina (Mljekarstvo)
Croatia has completely adopted the EU set up criteria for protection of agricultural products and foodstuffs through the implementation of two Regulations: Quality of the Protected Denomination of Origin and Protected Geographical Indication (NN.80/05) and Traditional Speciality Guaranteed (NN. 127/05). According to the results obtained from the four years research period on the production characteristics of the Pag sheep, milk and the Pag cheese quality, the essential description for certification and quality control of any autochthonous cheese are shown. Additionally, regardless from the arranged criteria for protection, other legal regulations that cheeses have to comply with are also described.